Organoleptic characteristics of melon fruits intended for storage - Davletbayevich, Sultanov Jetkerbay; Ergashevich, Umidov Shavkat (Journal of Medical Genetics and Clinical Biology, 2024)
In the article, the results of the research carried out for the purpose of studying the organoleptic characteristics of melon fruits intended for storage are given with an in-depth scientific analysis.